Greening the Information and Communication Technology in the Education Sector: Malaysian Teachers’ Perspective - Sathivelu, Muttamah; Zan, Zainal Md (CENTRAL ASIA AND THE CAUCASUS, 2021)
Dawning of the digital era has brought about tremendous change in humans livelihood and the way we interact with one another. Information and communication technology (ICT) has become a part of our lives that we are not willing to forgo for any matter. Whilst we are racing in the digital world, researchers found that ICT can be huge problem to the environment if mismanaged. ICT infrastructures can be huge burden to the electricity grid and not to miss the accumulation of e-waste with the rate of obsolescence of the technology. Malaysia is still far lagging in creating awareness among the citizens even though we have a well decorated policy on green technology. This research was conducted to determine the level of awareness on green ICT practices among teachers in Malaysia and the issues that deter the implementation of these green practices. A number of 930 teachers participated in the survey from all over Malaysia and their opinion was also recorded for analysis. The findings show that the level of awareness of green ICT practices is moderate among teachers and serious measures need to be taken by the administrators if we want to sustain our environment for generations to come.